HUBUNGAN PERSALINAN KPD DENGAN KEJADIAN SEPSIS NEONATORUM DI RUANG PERINATOLOGI RS WIJAYA KUSUMA LUMAJANG - Husnul Khotimah; Sri Wahyuningsih; Agustina Widayati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The problem of maternal and infant morbidity and mortality in Indonesia is still a big problem. Maternal and infant mortality rates are one of the indicators in determining health status and the success of implementing health development. The Indonesian government is still trying to reduce maternal and infant mortality by prioritizing these issues in health development. While the trend of child mortality from year to year shows a decline. In developing countries including Indonesia, neonatal sepsis has a major contribution to significant morbidity and mortality rates. The purpose of this study was to analyze the relationship between PROM delivery and the incidence of neonatal sepsis. This research is an analytic observational study using a cross sectional approach. The data was taken from the medical records of patients at Wijaya Kusuma Hospital during the range of January 2021 to June 2022. The number of research samples was 232 respondents and was taken using a total sampling technique based on inclusion and exclusion criteria. Analyzed and tested spearman rank correlation using SPSS ver 2.0. Most of the respondents were <72 hours old and some of the respondents were male, most of the respondents were born with a history of premature rupture of membranes, most of the respondents had neonatal sepsis. There is a relationship between premature rupture of membranes and the incidence of neonatal sepsis in the Perinatology Room of Wijaya Kusuma Hospital Lumajang with p = 0.000 and r value = 0.517 indicating that the two variables have a strong relationship and a positive r value indicates that the relationship between the two variables is unidirectional.